Rare earth metal doped high-temperature-resistant polyimide composite material as well as preparation method and application thereof

By preparing nanofillers on the surface of rare earth metal oxides, combined with cerium oxide and other materials, the problem of insufficient mechanical properties of polyimide composite materials in the prior art is solved, and the improvement of high-temperature durability and mechanical properties is achieved. , suitable for large-scale production.

CN119264427APending Publication Date: 2025-01-07AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411529605.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The high-temperature resistant polyimide composite materials prepared in the prior art have insufficient mechanical properties and are not suitable for large-scale production. The low degree of imidation leads to problems of high shrinkage, deflation and high residual stress.

Method used

Rare earth metal oxide nanofillers are prepared by grafting the modifier on the surface of rare earth metal oxides, enhancing the inter-chain effect of polyimide molecules, limiting the early relaxation of the molecular chain, improving temperature resistance and mechanical properties, and using rare earths The combination of metal oxides such as cerium oxide and modifiers improves the overall mechanical properties of the composite.

Benefits of technology

The temperature resistance and mechanical properties of polyimide are significantly improved, and the rapid and large-scale preparation is achieved, the tensile strength reaches ≥160MPa, and the high temperature resistance of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264427A_ABST
    Figure CN119264427A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a high-temperature-resistant polyimide composite material. The polyimide composite material comprises polyimide and a rare-earth metal oxide nanofiller, the rare earth metal oxide nano-filler comprises a rare earth metal oxide and a modifier grafted on the surface of the rare earth metal oxide. By adding the rare earth metal oxide nanofiller, the temperature resistance of polyimide is remarkably improved, and the prepared polyimide composite material has excellent temperature resistance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide materials, and in particular relates to a high-temperature resistant polyimide composite material and a preparation method and application thereof. Background Art

[0002] Polyimide (PI) is a type of polymer with excellent properties, which is widely used in aerospace, optics, microelectronics and other fields. However, as PI composite materials are used as structural composite materials in the aerospace field. Therefore, higher requirements are placed on PI composite materials. In order to improve the temperature resistance of PI, the traditional chemical modification method is to use the chemical properties of the PI cross-linked structure to design the molecular structure, which includes the use of an optimized combination of mature monomers, the introduction of heat-resistant characteristic groups on the molecular chain, etc., to improve the temperature resistance of PI on the basis of ensuring the glass transition temperature and process performance, so that it can meet the long-term use requirements in specific high-temperature service environments.

[0003] CN115490858A discloses a preparation method and application of a high temperature resistant polyimide composite material, the preparation method comprising the following steps: (1) dissolving 4,4′-diaminodiphenyl ether and 4,4′-dibenzophenone tetracarboxylic dianhydride containing heteropyrene structure in N,N-dimethylformamide polar solvent, then adding 3,3′,4,4′-biphenyltetracarboxylic dianhydride monomer to react for 15 hours to obtain a glue having a certain viscosity, (2) then coating the glue on a substrate, drying to remove the solvent, and then using a thermal imidization method to obtain a high temperature resistant polyimide. This technical solution can realize the preparation of high temperature resistant polyimide, but since the polyimide prepared by this chemical modification method has a large side chain group, the increase in molecular elasticity will lead to a decrease in the mechanical properties of the material. In addition, this method is not suitable for molecular level design modification and is not suitable for large-scale production and preparation.

[0004] Similarly, CN116162242A also discloses a preparation method and application of a high-temperature resistant polyimide composite material, the preparation method comprising the following steps: (1) under inert protection, aromatic dianhydride monomers are mixed with polar aprotic solvents, and then aromatic diisocyanate is added dropwise to the above solution, and after the addition is completed, the reaction is kept at 60°C for 4 hours; (2) triethylamine catalyst is finally added, and the temperature is raised to 90°C and the reaction is continued for 10 hours; (3) the polyimide solution is cooled to room temperature and then dispersed in an organic solvent, the precipitate is collected, and dried to obtain the high-temperature resistant polyimide composite material. The technical solution can prepare high-temperature resistant polyimide. Since the organic alkaline catalyst in this method limits the extension of the molecular chain, the mechanical properties of the prepared polyimide composite material are affected, and the low degree of imidization causes problems such as high shrinkage, degassing and high residual stress.

[0005] Therefore, it is necessary to develop a polyimide composite material that is resistant to high temperatures and has excellent mechanical properties. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a high temperature resistant polyimide composite material and a preparation method and application thereof. The polyimide composite material has excellent high temperature resistance and mechanical properties and can be prepared quickly and on a large scale.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a high temperature resistant polyimide composite material, the high temperature resistant polyimide composite material comprising polyimide and rare earth metal oxide nanofiller; the rare earth metal oxide nanofiller comprising rare earth metal oxide and a modifier grafted on the surface of the rare earth metal oxide.

[0009] In the present invention, a rare earth metal oxide nanofiller is prepared by grafting a modifier onto the surface of a rare earth metal oxide. The rare earth metal oxide nanofiller can enhance the interaction between polyimide molecular chains, limit the early relaxation of the molecular chains, significantly improve the temperature resistance of the polyimide, and effectively improve the mechanical properties.

[0010] Preferably, the rare earth metal oxide includes any one of zirconium oxide, cerium oxide, neodymium oxide, hafnium oxide, gadolinium oxide and lanthanum oxide, or a combination of at least two thereof, and more preferably cerium oxide.

[0011] In the present invention, the rare earth metal oxide is preferably cerium oxide, because the empty orbitals of the outer layer of the cerium oxide make them have extremely strong coordination, and the polymer can form a corresponding polymer complex with the cerium element, effectively improving the mechanical properties of the composite material.

[0012] Preferably, the modifying agent comprises silicone compound, polydopamine, polyvinyl alcohol and chitosan.

[0013] Preferably, the siloxane compound includes any one or a combination of at least two of γ-aminopropyltriethoxysilane (KH-550), vinyltriethoxysilane (KMB5220), γ-aminopropyltrimethoxysilane (WD-56) and γ-(β-aminoethyl)aminopropyltrimethoxysilane (KH-791).

[0014] Preferably, the rare earth metal oxide nanofiller is prepared by the following method: dissolving the rare earth metal oxide and the modifier in an anhydrous ethanol solution, heating the mixed solution, and then filtering and separating the mixed solution, drying and grinding the mixed solution to obtain the rare earth metal oxide nanofiller.

[0015] In the present invention, the modifier is grafted onto the surface of the rare earth metal oxide by a chemical method. The cerium oxide grafted modifier can increase the surface energy of the nanofiller and can also serve as a cross-linking agent to improve the overall mechanical properties of the composite material.

[0016] Preferably, the anhydrous ethanol is 100-150 mL (e.g., 100 mL, 105 mL, 110 mL, 115 mL, 120 mL, 125 mL, 130 mL, 135 mL, 140 mL, 145 mL or 150 mL, etc.).

[0017] Preferably, the heating time is 1-3h (e.g., 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h or 2.8h, etc.), and the heating temperature is 50-120℃ (e.g., 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃, etc.).

[0018] Preferably, the negative pressure of the filtration is 0.1-1 MPa, and the filtration time is 1-5 h.

[0019] Preferably, the mass ratio of the rare earth metal oxide to the modifier is 1.5-6:1, for example, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, 5.0:1, 5.5:1 or 6.0:1, etc.

[0020] In the present invention, the mass ratio of the rare earth metal oxide to the modifier is 1.5-6:1. If the mass ratio of the rare earth metal oxide to the modifier is too large, the surface energy of the rare earth metal oxide will be too low, so that the crosslinking property between the nanofiller and the composite material will be reduced; if the mass ratio of the rare earth metal oxide to the modifier is too small, it will lead to excessive modifier, causing the nanofiller to agglomerate.

[0021] Preferably, based on the total mass of the high temperature resistant polyimide composite material as 100%, the mass percentage of the polyimide is 96-98% (for example, 96.2%, 96.4%, 96.6%, 96.8%, 97%, 97.2%, 97.4%, 97.6% or 97.8%, etc.), the mass percentage of the rare earth metal oxide is 1.5-3% (for example, 1.6%, 1.7%, 1.9%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc.), and the mass percentage of the modifier is 0.5-2.5% (for example, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9% or 0.95%, etc.).

[0022] In the present invention, taking the total mass of the high-temperature resistant polyimide composite material as 100%, the mass percentage of the polyimide is 96-98%. If the mass percentage of the polyimide is too large, the temperature resistance of the polyimide composite material cannot be improved due to too little rare earth metal oxide nanofiller added; if the mass percentage of the polyimide is too small, excessive addition of rare earth metal oxide nanofiller will cause local agglomeration in the polyimide matrix, affecting the mechanical properties of the composite material.

[0023] Preferably, the raw materials for preparing the polyimide include diamine compounds and dianhydride compounds.

[0024] Preferably, the diamine compound includes 3,4-diaminodiphenyl ether and / or 4,4-diaminobenzophenone and / or 4,4-diaminodiphenylmethane.

[0025] Preferably, the dianhydride compound includes 4-(ethynyl-1,2-diyl) diphthalic anhydride and / or 2,3',3,4'-biphenyltetracarboxylic dianhydride.

[0026] Preferably, the raw materials for preparing the polyimide include 3,4-diaminodiphenyl ether and 2,3',3,4'-biphenyltetracarboxylic dianhydride.

[0027] In a second aspect, the present invention provides a method for preparing the high temperature resistant polyimide composite material as described in the first aspect, the preparation method comprising the following steps: dissolving a diamine compound, a dianhydride compound and a rare earth metal oxide nanofiller in a solvent, and reacting by stirring to obtain the high temperature resistant polyimide composite material.

[0028] Preferably, the preparation method specifically comprises the following steps:

[0029] (1) In an inert gas atmosphere, a diamine compound is dissolved in a solvent and stirred continuously until transparent, and then a dianhydride compound is added to the solution in 4-6 portions, and then a rare earth metal oxide nanofiller is added and stirred for 1-3 hours to obtain a mixed solution.

[0030] (2) coating the mixed solution obtained in step (1) on a quartz glass plate and reacting it in a high-temperature oven, and after the reaction is completed, obtaining the high-temperature resistant polyimide composite material.

[0031] Preferably, the inert gas includes any one of helium, argon or nitrogen, or a combination of at least two of them.

[0032] Preferably, the concentration of the diamine compound in the mixed solution of step (1) is 0.1-0.5 g / mL, for example, 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL or 0.5 g / mL.

[0033] Preferably, the concentration of the dianhydride compound in the mixed solution of step (1) is 0.1-0.5 g / mL, such as 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL or 0.5 g / mL.

[0034] Preferably, the concentration of the inorganic nanofiller in the mixed solution of step (1) is 0.04-0.15 mg / mL, for example 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 0.1 mg / mL, 0.11 mg / mL, 0.12 mg / mL, 0.13 mg / mL, 0.14 mg / mL or 0.15 mg / mL, etc.

[0035] Preferably, the reaction comprises reacting at 50-100° C. (e.g., 50° C., 60° C., 70° C., 80° C., 90° C., or 100° C., etc.) for 2-3 h (e.g., 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h, or 3.0 h, etc.), raising the temperature to 100-250° C. (e.g., 100° C., 130° C., 160° C., 190° C., 220° C., or 250° C., etc.) for the reaction. The reaction mixture is reacted for 2-3h (e.g., 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, etc.), and then reacted at 250-350°C (e.g., 250°C, 270°C, 290°C, 310°C, 330°C or 350°C, etc.) for 1-5h (e.g., 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h or 5.0h, etc.).

[0036] Preferably, the reaction comprises reacting at 100-250°C (e.g., 250°C, 270°C, 290°C, 310°C, 330°C or 350°C, etc.) for 2-5h (e.g., 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, etc.), and then reacting at 250-350°C (e.g., 250°C, 270°C, 290°C, 310°C, 330°C or 350°C, etc.) for 1-5h (e.g., 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h or 5.0h, etc.).

[0037] Preferably, the solvent comprises a polar aprotic solvent.

[0038] Preferably, the polar aprotic solvent includes any one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF) or N-dimethylpyrrolidone (NMP) or a combination of at least two thereof.

[0039] In a third aspect, the present invention provides an application of the high temperature resistant polyimide composite material as described in the first aspect in a functional polymer film material and a carbon fiber reinforced polyimide composite material.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The invention significantly enhances the temperature resistance of polyimide by adding the rare earth metal oxide nanofiller, and prepares a high temperature resistant polyimide composite material, wherein the rare earth metal oxide nanofiller is formed by modifying a rare earth metal compound. The high temperature resistant polyimide composite material has the characteristics of excellent temperature resistance and mechanical properties. The tensile strength of the high temperature resistant polyimide composite material is ≥160MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a microscopic morphology of the rare earth metal oxide nanofiller doped polyimide composite material. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] Example 1

[0045] The present embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof. The high temperature resistant polyimide composite material includes polyimide and rare earth metal compound nanofiller. The rare earth metal compound nanofiller includes rare earth metal oxide (cerium oxide) and a modifier (KH-550) grafted on the surface of the rare earth metal oxide.

[0046] Taking the total mass of the high-temperature resistant polyimide composite material as 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal oxide is 1.5%, and the mass percentage of the modifier is 0.5%.

[0047] The preparation method of the rare earth metal oxide nanofiller is as follows:

[0048] 0.045 g of cerium oxide and 0.015 g of KH-550 (γ-aminopropyltriethoxysilane) were dissolved in anhydrous ethanol, and after being fully stirred, they were heated in an 80° C. oil bath for 3 h. After the sample was cooled, it was filtered and separated under a negative pressure of 1 MPa, and the rare earth metal oxide nanofiller was obtained after drying.

[0049] The preparation method of the polyimide composite material is as follows:

[0050] (1) Pour 50 mL of N,N-dimethylacetamide into a flask and replace the air in the flask with an inert gas to serve as a protective gas; add 1.5 g of 3,4-diaminodiphenyl ether and stir the solution for 2 h until it becomes transparent, then add 1.5 g of 2,3',3,4'-biphenyltetracarboxylic anhydride divided into 4 portions into the flask every 30 min; add 0.06 g of a rare earth metal oxide nanofiller and stir for 3 h to obtain a mixed solution.

[0051] (2) The mixed solution obtained in step (1) is evenly coated on a quartz glass plate, and the solution is evenly coated with an applicator, and then the glass plate loaded with the solution is placed in a high-temperature oven, first dried at 100° C. for 2 hours, then the temperature is increased to 250° C. for drying for 2 hours, and finally dried at 350° C. for 3 hours. After the oven is cooled to room temperature, the material is removed from the glass plate by an immersion method, and dried at 60° C. for one night to obtain the high-temperature resistant polyimide composite material. Figure 1 This is a microscopic morphology of the rare earth metal oxide nanofiller doped polyimide composite material of this embodiment.

[0052] Example 2

[0053] The present embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof. The high temperature resistant polyimide composite material includes polyimide and rare earth metal compound nanofiller. The rare earth metal compound nanofiller includes rare earth metal oxide (zirconium oxide) and a modifier (KH-550) grafted on the surface of the rare earth metal oxide.

[0054] Taking the total mass of the high-temperature resistant polyimide composite material as 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal oxide is 1.5%, and the mass percentage of the modifier is 0.5%.

[0055] The preparation method of the rare earth metal oxide nanofiller is as follows:

[0056] 0.045g of zirconium oxide and 0.015g of KH-550 (γ-aminopropyltriethoxysilane) were dissolved in anhydrous ethanol, and after being fully stirred, they were heated in an 80°C oil bath for 3h. After the sample was cooled, it was filtered and separated under a negative pressure of 1MPa, and the rare earth metal oxide nanofiller was obtained after drying.

[0057] The preparation method of the polyimide composite material is as follows:

[0058] (1) Pour 50 mL of N,N-dimethylacetamide into a flask and replace the air in the flask with an inert gas to serve as a protective gas; add 1.5 g of 3,4-diaminodiphenyl ether and stir the solution for 2 h until it becomes transparent, then add 1.5 g of 2,3',3,4'-biphenyltetracarboxylic anhydride divided into 4 portions into the flask every 30 min; add 0.06 g of a rare earth metal oxide nanofiller and stir for 3 h to obtain a mixed solution.

[0059] (2) The mixed solution obtained in step (1) is evenly coated on a quartz glass plate, and the solution is evenly coated with an applicator, and then the glass plate loaded with the solution is placed in a high-temperature oven, first dried at 100° C. for 2 hours, then the temperature is increased to 250° C. for drying for 2 hours, and finally dried at 350° C. for 3 hours. After the oven is cooled to room temperature, the material is removed from the glass plate by an immersion method, and dried at 60° C. for one night to obtain the high-temperature resistant polyimide composite material.

[0060] Example 3

[0061] The present embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof. The high temperature resistant polyimide composite material includes polyimide and rare earth metal compound nanofiller. The rare earth metal compound nanofiller includes rare earth metal oxide (cerium oxide) and a modifier (WD-56) grafted on the surface of the rare earth metal oxide.

[0062] Taking the total mass of the high-temperature resistant polyimide composite material as 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal oxide is 1.5%, and the mass percentage of the modifier is 0.5%.

[0063] The preparation method of the rare earth metal oxide nanofiller is as follows:

[0064] 0.045g of zirconium oxide and 0.015g of WD-56 (γ-aminopropyltrimethoxysilane) were dissolved in anhydrous ethanol, and after being fully stirred, they were heated in an 80°C oil bath for 3h. After the sample was cooled, it was filtered and separated under a negative pressure of 1MPa, and the rare earth metal oxide nanofiller was obtained after drying.

[0065] The preparation method of the polyimide composite material is as follows:

[0066] (1) Pour 50 mL of N,N-dimethylacetamide into a flask and replace the air in the flask with an inert gas to serve as a protective gas; add 1.5 g of 3,4-diaminodiphenyl ether and stir the solution for 2 h until it becomes transparent, then add 1.5 g of 2,3',3,4'-biphenyltetracarboxylic anhydride divided into 4 portions into the flask every 30 min; add 0.06 g of a rare earth metal oxide nanofiller and stir for 3 h to obtain a mixed solution.

[0067] (2) The mixed solution obtained in step (1) is evenly coated on a quartz glass plate, and the solution is evenly coated with an applicator, and then the glass plate loaded with the solution is placed in a high-temperature oven, first dried at 100° C. for 2 hours, then the temperature is increased to 250° C. for drying for 2 hours, and finally dried at 350° C. for 3 hours. After the oven is cooled to room temperature, the material is removed from the glass plate by an immersion method, and dried at 60° C. for one night to obtain the high-temperature resistant polyimide composite material.

[0068] Example 4

[0069] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 95%, the mass percentage of the rare earth metal oxide is 3.75%, and the mass percentage of the modifier is 1.25%.

[0070] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal oxide nanofiller is adjusted to 0.048 g, and the rest is the same as in Example 1.

[0071] Example 5

[0072] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 96%, the mass percentage of the rare earth metal oxide is 3.0%, and the mass percentage of the modifier is 1.0%.

[0073] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal oxide nanofiller is adjusted to 0.036 g, and the rest is the same as in Example 1.

[0074] Example 6

[0075] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 97%, the mass percentage of the rare earth metal oxide is 2.25%, and the mass percentage of the modifier is 0.75%.

[0076] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal oxide nanofiller is adjusted to 0.024 g, and the rest is the same as in Example 1.

[0077] Example 7

[0078] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal oxide is 1.5%, and the mass percentage of the modifier is 0.5%.

[0079] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal oxide nanofiller is adjusted to 0.012 g, and the rest is the same as in Example 1.

[0080] Example 8

[0081] This embodiment provides a high temperature resistant polyimide composite material, which differs from Example 1 in that the 3,4-diaminodiphenyl ether is replaced by 4,4-diaminobenzophenone of the same mass, and the 2,3',3,4'-biphenyltetracarboxylic acid dianhydride is replaced by 4,4-(acetylene-1,2-diyl)phthalic anhydride of the same mass, and the rest is the same as Example 1.

[0082] Example 9

[0083] This embodiment provides a high temperature resistant polyimide composite material, which is different from Embodiment 1 in that the 3,4-diaminodiphenyl ether is replaced with 4,4-diaminodiphenylmethane of the same mass, and the rest is the same as Embodiment 1.

[0084] Example 10

[0085] This embodiment provides a high temperature resistant polyimide composite material, which is different from Embodiment 1 in that 2,3',3,4'-biphenyltetracarboxylic dianhydride is replaced with pyromellitic acid of the same mass, and other operations are the same as those of Embodiment 1.

[0086] Embodiment 11

[0087] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal compound is 1.5%, and the mass percentage of the modifier is 0.5%.

[0088] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal compound nanofiller is adjusted to 0.03 g, and the other steps are the same as those in Example 1.

[0089] Example 12

[0090] This embodiment provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Embodiment 1 only in that, based on the total mass of the polyimide composite material being 100%, the mass percentage of the polyimide is 98%, the mass percentage of the rare earth metal oxide is 1.5%, and the mass percentage of the modifier is 0.5%.

[0091] In the preparation method of the polyimide composite material, the addition amount of the rare earth metal oxide nanofiller is adjusted to 0.03 g, and the rest is the same as in Example 1.

[0092] Comparative Example 1

[0093] This comparative example provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Example 1 only in that the rare earth metal compound nanofiller is replaced with cerium oxide of the same mass;

[0094] Taking the total mass of the polyimide composite material as 100%, the mass percentage of the polyimide is 98%, and the mass percentage of the cerium oxide is 2%;

[0095] In the preparation method of the polyimide composite material, the rare earth metal compound nanofiller is replaced with cerium oxide of the same mass, and the rest is the same as in Example 1.

[0096] Comparative Example 2

[0097] This comparative example provides a high temperature resistant polyimide composite material and a preparation method thereof, which is different from Example 1 only in that the rare earth metal compound nanofiller is replaced with zirconium oxide of the same mass;

[0098] Taking the total mass of the polyimide composite material as 100%, the mass percentage of the polyimide is 98%, and the mass percentage of the zirconium oxide is 2%;

[0099] In the preparation method of the polyimide composite material, the rare earth metal compound nanofiller is replaced with zirconium oxide of the same mass, and the rest is the same as in Example 1.

[0100] The following performance tests were performed on the high temperature resistant polyimide composite materials provided in the examples and comparative examples:

[0101] (1) Tensile strength: Tested in accordance with GB / T 1040.1-2018. Test conditions refer to GB / T 1040.2-2006. The tensile strength test direction is vertical.

[0102] (2) High temperature resistance: The temperature resistance of the polyimide composite material was tested using a glass transition temperature tester. The test results are shown in Table 1.

[0103] Table 1 Tensile strength and high temperature resistance of composite materials

[0104] Tensile strength(MPa) Glass transition temperature(℃) Example 1 390 396 Example 2 394 398 Example 3 395 400 Example 4 396 412 Example 5 398 415 Example 6 442 422 Example 7 390 416 Example 8 395 400 Example 9 391 398 Example 10 395 403 Embodiment 11 405 413 Example 12 412 398 Comparative Example 1 373 385 Comparative Example 2 385 380

[0105] According to the test results in Table 1, the tensile strengths of the high temperature resistant polyimide composite materials provided in Examples 1-11 are 390, 394, 395, 396, 398, 442, 390, 395, 391, 395, 405, 412, 373 and 385 MPa, and the glass transition temperatures are 396, 398, 400, 412, 415, 422, 416, 400, 398, 403, 413, 398, 385 and 380°C.

[0106] Comparison between Example 1 and Examples 2-7 shows that, with the increase in the amount of rare earth metal oxide nanofiller added, the tensile strength and glass transition temperature of the polyimide composite material first increase and then decrease with the increase in the nanofiller.

[0107] By comparing Example 1 with Examples 8-10, it can be seen that different combinations of diamine compounds and dianhydride compounds also have an impact on the glass transition temperature of the obtained high-temperature resistant polyimide composite material. The high-temperature resistant polyimide composite material obtained by using 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene and pyromellitic anhydride (Example 10) has the highest glass transition temperature.

[0108] Compared with Example 1, if the addition amount of rare earth metal oxide nanofiller is too large (Example 11), the mechanical properties of the material are reduced; if the addition amount of rare earth metal oxide nanofiller is too small (Example 12), the glass transition temperature is reduced, which proves that the polyimide composite material containing a specific mass percentage of polyimide, rare earth metal compound and modifier has better temperature resistance.

[0109] Compared with Example 1, if the nanofiller is replaced with cerium oxide of the same mass (Comparative Example 1), the tensile strength of the polyimide composite material decreases and the glass transition temperature also decreases.

[0110] Compared with Example 1, if the nanofiller is replaced with zirconium oxide of the same mass (Comparative Example 2), the tensile strength of the polyimide composite material decreases and the glass transition temperature also decreases. It can be seen from Comparative Examples 11 and 12 that if the rare earth metal oxide is not modified, the mechanical properties and glass transition temperature of the composite material will decrease. This is mainly because the oxide powder is easy to agglomerate, and it is difficult for the rare earth metal compound to increase the interaction between the polyimide and the compound through the interface.

[0111] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a polyimide composite material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high temperature resistant polyimide composite material, characterized in that: The high temperature resistant polyimide composite material comprises polyimide and rare earth metal oxide nanofiller; the rare earth metal oxide nanofiller comprises rare earth metal oxide and a modifier grafted on the surface of the rare earth metal oxide.

2. The high temperature resistant polyimide composite material according to claim 1, characterized in that: The rare earth metal oxide includes any one of zirconium oxide, cerium oxide, neodymium oxide, hafnium oxide, gadolinium oxide and lanthanum oxide, or a combination of at least two of them; the modifier includes siloxane compounds, polydopamine, polyvinyl alcohol and chitosan; the siloxane compound includes any one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane and γ-(β-aminoethyl)aminopropyltrimethoxysilane, or a combination of at least two of them.

3. The high temperature resistant polyimide composite material according to claim 1 or 2, characterized in that: The rare earth metal oxide nanofiller is prepared by the following method: dissolving the rare earth metal oxide and the modifier in an anhydrous ethanol solution, heating the mixed solution, then filtering and separating, drying and grinding to obtain the rare earth metal oxide nanofiller; the anhydrous ethanol solvent is 100-500 mL; the heating temperature is 50-120° C., and the heating time is 1-3 h; the negative pressure of the filtration is 0.1-1 MPa, and the filtration time is 1-5 h; the mass ratio of the rare earth metal oxide to the modifier is 1.5-6:

1.

4. The high temperature resistant polyimide composite material according to claim 1, characterized in that: Taking the total mass of the polyimide composite material as 100%, the mass percentage of the polyimide is 96-98%, the mass percentage of the rare earth metal oxide is 1.5-3%, and the mass percentage of the modifier is 0.5-2.5%.

5. The high temperature resistant polyimide composite material according to claim 1, characterized in that: The raw materials for preparing the polyimide include diamine compounds and dianhydride compounds; the diamine compounds include 3,4-diaminodiphenyl ether and / or 4,4-diaminobenzophenone and / or 4,4-diaminodiphenylmethane; the dianhydride compounds include 4,4-(acetylene-1,2-diyl) diphthalic anhydride and / or 2,3',3,4'-biphenyltetracarboxylic anhydride.

6. A method for preparing a high temperature resistant polyimide composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: dissolving a diamine compound, a dianhydride compound and a rare earth metal oxide nanofiller in a solvent, and reacting the mixture by stirring to obtain the high temperature resistant polyimide composite material.

7. The preparation method according to claim 6, characterized in that: The preparation method specifically comprises the following steps: (1) In an inert gas atmosphere, a diamine compound is dissolved in a solvent, and the mixture is continuously stirred until transparent, and then a dianhydride compound is added to the solution in 4-6 portions, and then a rare earth metal oxide nanofiller is added and stirred for 1-3 hours to obtain a mixed solution; (2) coating the mixed solution obtained in step (1) on a quartz glass plate and reacting it in a high-temperature oven, and after the reaction is completed, obtaining the high-temperature resistant polyimide composite material.

8. The concentration of the diamine compound in the mixed solution of step (1) is 0.1-0.5 g / mL; the concentration of the dianhydride compound in the mixed solution of step (1) is 0.1-0.5 g / mL; the concentration of the rare earth metal oxide nanofiller in the mixed solution of step (1) is 0.04-0.15 mg / mL.

9. The preparation method according to claim 6 or 7, characterized in that: The reaction comprises reacting at 50-100° C. for 2-3 hours, raising the temperature to 100-250° C. for 2-3 hours, and then reacting at 250-350° C. for 1-5 hours; or, the reaction comprises reacting at 100-250° C. for 2-3 hours, and then reacting at 250-350° C. for 1-5 hours.

10. Use of the high temperature resistant polyimide composite material according to any one of claims 1 to 5 in functional polymer film materials and carbon fiber reinforced polyimide composite materials.

Citation Information

Cited By

  • Super-hydrophilic and oleophylic polymethacrylimide foam and preparation method thereof

    CN121293571A